2010
DOI: 10.1002/hipo.20844
|View full text |Cite
|
Sign up to set email alerts
|

Extinction of spatial memory alters CREB phosphorylation in hippocampal CA1

Abstract: Although the importance of cAMP-response element binding protein (CREB) phosphorylation in long-term memory formation is well documented for hippocampus-dependent tasks, little is known about the changes in phosphorylated CREB (pCREB) that occur during the process of extinction. The purpose of this study was to characterize the temporal patterns of pCREB in the CA1 and the amygdala after the extinction of previously acquired spatial information in the water maze. Mice were trained to find a hidden platform loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 61 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The hippocampal biochemical correlates of habituation to a new environment are similar to those of extinction (Vianna et al, 2000) or indeed to almost any other form of learning in mammals: initial activation of NMDA receptors, followed by that of various protein kinases, mainly the Erk kinases in hippocampus (Tronson et al, 2009(Tronson et al, , 2012Guedea et al, 2011) and amygdala (Lu et al, 2001); and protein kinase A (Tronson et al, 2012) followed by an increase of p-CREB in hippocampus (Porte et al, 2011) followed by the need for protein synthesis (Izquierdo et al, 2006;Tronson et al, 2009Tronson et al, , 2012Sacai et al, 2014;De Carvalho Myskiw et al, 2014). Recently, a phosphodiesterase-4 mediated switch between the strengthening of a fear memory and its extinction has been suggested (Roesler et al, 2014).…”
Section: A Note On Habituation Learningmentioning
confidence: 77%
“…The hippocampal biochemical correlates of habituation to a new environment are similar to those of extinction (Vianna et al, 2000) or indeed to almost any other form of learning in mammals: initial activation of NMDA receptors, followed by that of various protein kinases, mainly the Erk kinases in hippocampus (Tronson et al, 2009(Tronson et al, , 2012Guedea et al, 2011) and amygdala (Lu et al, 2001); and protein kinase A (Tronson et al, 2012) followed by an increase of p-CREB in hippocampus (Porte et al, 2011) followed by the need for protein synthesis (Izquierdo et al, 2006;Tronson et al, 2009Tronson et al, , 2012Sacai et al, 2014;De Carvalho Myskiw et al, 2014). Recently, a phosphodiesterase-4 mediated switch between the strengthening of a fear memory and its extinction has been suggested (Roesler et al, 2014).…”
Section: A Note On Habituation Learningmentioning
confidence: 77%
“…For example, training in the water maze leads to biphasic changes in phosphorylation of cAMP-response element-binding protein (CREB) in the CA1 area of the hippocampus, with two different peaks occurring 15 min and 8 h post-acquisition (Porte et al, 2011). Also, in the CA1, training in tone-shock fear conditioning leads to a monophasic increase in phosphorylation (15 min following training) of extracellular signal-regulated kinase 1/2 (ERK) and CREB, while context-shock conditioning leads to a biphasic increase in ERK/CREB phosphorylation (Trifilieff et al, 2006).…”
Section: The Biphasic Shifts In Stathmin and Microtubules Confirmmentioning
confidence: 99%
“…There is a body of evidence supporting the idea that the amygdala complex is involved in spatial memory. Specifically, Porte et al [16] have shown an active role of the amygdala, together with the hippocampus, both in early and late stages of the extinction of spatial memory. These authors suggest a regulatory role for the amygdala during the extinction process, modulating the hippocampus-based non-emotional aspects and the amygdala-dependent emotional processes that spatial learning in the water maze involves.…”
Section: Brain Co Activity Changes and Reorganization Of Functional Nmentioning
confidence: 99%
“…In this regard, some authors have tried to establish a map of the involved structures in spatial memory extinction, highlighting the role played by the amygdala and the hippocampus [16]. In addition, the mammillary bodies and the medial prefrontal cortex have been largely related with spatial navigation [17][18][19] and memory extinction processes [20,21].…”
Section: Introductionmentioning
confidence: 99%